Flexible replica placement for enhancing the availability in edge computing environment - Li, Chunlin; Wang, YaPing; Tang, Hengliang; Zhang, Yujiao; Xin, Yan; Luo, Youlong (Computer communications, 2019)
As edge devices that make up the Internet become more powerful, these devices in edge computing environment will even perform better in improving the computing and storage capabilities of system. In this paper, to enhancing data availability and improve cloud storage performance in edge computing environment, an adaptive replica placement strategy in edge computing environment is proposed to study the relationship among user access characteristics, the number of replicas, and the replicas location. To deal with the volatility of user access, the strategy in this paper takes data block as the data unit and the dynamic replica creation algorithm (DRC-GM) is proposed. DRC-GM uses the relationship between access frequency of data blocks and the number of replicas to dynamically adjust the number of replicas to ensure data availability requirements. To find the optimal location for replica distributed placement, in this paper, the replica placement algorithm (RP-FNSG) is proposed. And replica number, node performance and replica consistency are considered. Experiment results show that DRC-GM and RP-FNSG algorithms in edge computing environment can greatly improve system performance in terms of better prediction accuracy, shorter access response, higher effective network and storage space usage, which enhancing the data availability.